Dynamics of IL‐15/IL‐15R‐α expression in response to HSV‐1 infection reveal a novel mode of viral immune evasion counteracted by iNKT cells. Issue 3 (26th December 2021) - Sobkowiak, Michał J.; Paquin‐Proulx, Dominic; Bosnjak, Lidija; Moll, Markus; Sällberg Chen, Margaret; Sandberg, Johan K.
Abstract: Herpes simplex virus type 1 (HSV‐1) infects and persists in most of the human population. Interleukin‐15 (IL‐15) has an important role in the activation of cell‐mediated immune responses and acts in complex with IL‐15 receptor alpha (IL‐15R‐α) through cell surface transpresentation. Here, we have examined the IL‐15/IL‐15R‐α complex response dynamics during HSV‐1 infection in human keratinocytes. Surface expression of the IL‐15/IL‐15R‐α complex rapidly increased in response to HSV‐1, reaching a peak around 12 h after infection. This response was dependent on detection of viral replication by TLR3, and enhancement of IL15 and IL15RA gene expression. Beyond the peak of expression, levels of IL‐15 and IL‐15R‐α gradually declined, reaching a profound loss of surface expression beyond 24 h of infection. This involved the loss of IL15 and IL15RA transcription. Interestingly, invariant natural killer T (iNKT) cells inhibited the viral interference with IL‐15/IL‐15R‐α complex expression in an IFNγ‐dependent manner. These results indicate that rapid upregulation of the IL‐15/IL‐15R‐α complex occurs in HSV‐1 infected keratinocytes, and that this response is targeted by viral interference. Shutdown of the IL‐15 axis represents a novel mode of HSV‐1 immune evasion, which can be inhibited by the host iNKT cell response. Abstract : Infection of human keratinocytes with HSV‐1 initially triggers upregulation of cell surface IL‐15/IL‐15R‐α via TLR3. This effect is inhibited by the virus and resulting in downregulation of the IL‐15/IL‐15R‐α complex. iNKT cells counteracts this viral immune evasion via IFNγ.